IMPLEMENTASI NILAI-NILAI PANCASILA DALAM ERA â€œNEW NORMALâ€ - Mirnawati, Sri (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2021)
The Covid-19 pandemic that Indonesia has been facing since March 2020 requires well-planned handling to deal with this new normal or new normal. Adopt health protocols that are in accordance with World Health Organization (WHO) directives that apply globally to strengthen community resilience in the face of the Covid-19 pandemic. Through various policies that have been established by the Government of Indonesia to respond to this Covid-19 pandemic health disaster. The level of transmission and spread of Covid-19 is still increasing and there has not been a significant decrease because the implementation of policies that handle Covid-19 which refers to WHO directives are still faced with many problems so that the handling is still not optimal and effective. Therefore, it is necessary to change the approach to handling the Covid-19 pandemic which is based on the values of Pancasila as a view of the life philosophy of the nation and the Indonesian people when viewed from the perspective of national interests, which is expected to increase the useful results of the efforts to handle the Covid-19 pandemic carried out by the Government. The implementation of Pancasila values in handling the Covid-19 pandemic can create a new normal or a new normal that is free from Covid-19.